(3cJGH GdaUhd aj GdLOds - (3GHf Ybjd GdHZOGOj GdMfHdj,J (B553 (3g` s
(3ChdgG (B:s
(3jHJOF Hbhdg bGd GdeLGOd hGYJHQ eG PcQfGg ai GdefGXQI eJi bdJ dh hLHJ GdRcGI Ydi GdeOjhf dhLHJ Ydi GdabjQ EeG HGdfU Ch HGdbjGS Ch HZjQgG ef GdOdGFd s
(3BNQgG (B:s
(3hPdc dGjbOM ai chfg KGHJkG ai faS GdGeQ adG JZad Yf GdaQb Hjf JbOjQ GdGehQ GdhGbYI hJbOjQ EfVeGe GdeOYi EdjgG BNQ GdcJGH hGdMeO ddg Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdadSaI hGdefWbs